Towards a comprehensive framework of social presence for online, hybrid, and blended learning - Kreijns, Karel; Yau, Jane; Weidlich, Joshua; Weinberger, Armin (Frontiers in Education, 2024)
Social presence, which refers to the psychological phenomenon of perceiving other persons in technology mediated communication as 'real' and with whom one can connect, has gained an increasing interest by teachers and researchers involved in designing online, hybrid, and blended learning environments, particularly group learning settings known as computer-supported collaborative learning (CSCL). While some scholars attribute social presence primarily to the physical attributes of communication media, others emphasize the importance of social contextual and individual factors. Despite considering these factors, they still cannot fully explain the varying degrees of social presence experienced across different communication and collaboration modes and modalities. Consequently, there is a need for a more comprehensive theoretical account on the antecedents of social presence. In this article we propose such an account that integrates the social information processing (SIP) theory, construal level theory (CLT), and telepresence theory into one social presence framework. In line with CLT, we propose that social presence is also influenced by the impressions (construals) we construct from other persons not only through the accumulation of messages over time but also through the psychological distance we feel to those persons, which may be imposed by features of the communication media or realities of the learning context. Further, in line with telepresence theory, we propose that social presence is influenced by the sense of being ‘present’ in the remote physical or virtual place, as this is where other salient persons ‘are.’ This comprehensive theoretical framework allows us to understand varying degrees of social presence while in (pseudo) real-time and asynchronous communication and collaboration using a variety of different communication media ranging from text-based (e.g., e-mail, instant text messaging) to immersive (e.g., 3D computer generated; a physical remote place).